2011
DOI: 10.1007/s10482-011-9670-2
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of anaerobic elemental sulfur oxidation by ferric iron in Acidithiobacillus ferrooxidans and protein identification by comparative 2-DE-MS/MS

Abstract: Elemental sulfur oxidation by ferric iron in Acidithiobacillus ferrooxidans was investigated. The apparent Michaelis constant for ferric iron was 18.6 mM. An absence of anaerobic ferric iron reduction ability was observed in bacteria maintained on elemental sulfur for an extended period of time. Upon transition from ferrous iron to elemental sulfur medium, the cells exhibited similar kinetic characteristics of ferric iron reduction under anaerobic conditions to those of cells that were originally maintained on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
29
0

Year Published

2012
2012
2014
2014

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 62 publications
2
29
0
Order By: Relevance
“…Although Fe 3+ reduction is widespread in acidophilic microorganisms [ 95 , 96 ], little is known about the precise enzymes and pathways involved. In A. ferroxidans, a c -type cytochrome has been implicated in ferric iron respiration [ 97 ] as has a rusticyanin [ 98 ]. Rusticyanin proteins are found annotated only in S. thermosulfidooxidans and AMDSB5, and membrane-bound c- type cytochrome proteins are found in all Sulfobacillus genomes except AMDSBA1.…”
Section: Resultsmentioning
confidence: 99%
“…Although Fe 3+ reduction is widespread in acidophilic microorganisms [ 95 , 96 ], little is known about the precise enzymes and pathways involved. In A. ferroxidans, a c -type cytochrome has been implicated in ferric iron respiration [ 97 ] as has a rusticyanin [ 98 ]. Rusticyanin proteins are found annotated only in S. thermosulfidooxidans and AMDSB5, and membrane-bound c- type cytochrome proteins are found in all Sulfobacillus genomes except AMDSBA1.…”
Section: Resultsmentioning
confidence: 99%
“…ferrooxidans showed upregulation of sulfide/quinone oxidoreductase ( sqr ) and proteins involved in cell envelope biogenesis (Kucera et al ., 2012). In addition, proteins previously attributed to electron transport during aerobic Fe 2+ oxidation, including rusticyanin and cytochrome c 552 , were also found to be upregulated (Kucera et al ., 2012). This observation has been confirmed in a combined proteomic and transcriptomic study of S ° ‐grown At.…”
Section: Sulfur Metabolism In Acidophilic Prokaryotesmentioning
confidence: 99%
“…Tetrathionate reductase (TetH) (28) and ArsH (29) have been proposed to be candidates for the final electron donor to Fe 3ϩ . In addition, Kucera et al (30) found a significant increase in the abundance of electron transporters, such as rusticyanin and cytochrome c 552 (which are known to be involved in Fe 2ϩ oxidation), in cultures of A. ferrooxidans grown anaerobically on Fe 3ϩ . These authors suggested that rus operon-encoded proteins were involved in both Fe 2ϩ oxidation and Fe 3ϩ reduction in this acidophile.…”
mentioning
confidence: 99%